EFFICIENCY OF A LAMINAR SEDIMENTER AND CONVENTIONAL TO ELIMINATE SOLIDS - Guerrero Vejarano, Tania E. (2020)
The objective of this research was to determine the efficiency of the laminar and conventional sedimentation system to eliminate different concentrations of suspended solids, for which different physicochemical parameters were taken into account (temperature, pH, turbidity, dissolved oxygen and dry residue). To determine the physicochemical parameters, water samples were prepared at different concentrations (1, 2 and 3%) of solids, which were analyzed at the inlet and outlet of the settler, in treatments with coagulant and without coagulant, with three repetitions at each treatment. To determine which of the sedimentation was more efficient, analysis of variance and Tukey test of the evaluated factors (type of settler, coagulant and concentration of solids) were performed, obtaining as a result significant differences between both settlings with